The clinical use of remote parameter testing during cardiac implantable electronic devices implantation procedures: a single center, randomized, open-label, non-inferiority trial - Xiong, Shiqiang; Qin, Shujuan; Tong, Lin; Long, Yu; Luo, Yan; Feng, Qiao; Peng, Xiufen; Jiang, Maoling; Xiong, Feng; Li, Jin; Zhang, Yangchun; Zhang, Zhen; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background: A novel non-contact system for remote parameter testing and reprogramming offers an alternative method for assessing device parameters during cardiac implantable electronic devices (CIEDs) implantation without the need for physical contact with the manufacturer's clinical service technician. The safety and feasibility of using this system in CIEDs implantation procedures remains to be determined.Objective: Evaluate the safety and feasibility of remote parameter testing in CIEDs implantation procedures.Methods: A single center, randomized, open-label, non-inferiority trial (ChiCTR2200057587) was conducted to compare the two approaches for interrogating CIEDs during implantation procedures: routine interrogation performed by on-site technicians or remote interrogation performed by technicians using the 5G-Cloud Technology Platform. Patients aged ≥18 years and elected to receive CIEDs were eligible for inclusion. The primary endpoint was the completion rate of the parameter test. Safety and efficiency were evaluated in all randomly assigned participants.Results: A total of 480 patients were finally enrolled and were randomly assigned to routine group (n=240) or remote group (n=240). The primary endpoint was achieved by 100% in both groups ((P=0.0060 for noninferiority). The parameters of sensing, threshold, and impedance regarding the right atrium, right ventricle, and left ventricle had no statistical significance between the two groups (P > 0.05). Procedure time, parameter testing time, and both duration and dose of X-ray irradiation were not significantly different between the two groups (P > 0.05). Shut-open door frequency was significantly higher in the routine group than the remote group [6.00 (4.00, 8.00) vs 0, P < 0.0001]. Notably, no clinical or technical complications were observed in the remote group.Conclusions: Remote parameter testing is safe and feasible across various devices implantation procedures. The utilization of remote parameter testing and reprogramming could represent an innovative approach to improve healthcare accessibility and unlock the full potential of secondary centers in managing CIEDs.